PRECARIZAÇÃO DO TRABALHO DOCENTE: análise em uma IES privada de São Luís - MA - NUNES, Jaylson Franklin Mendonça (2023)
This dissertation deals with the precariousness of teaching work in private higher education as a result of advances in capital. The general objective is to analyze the main determinants of the precariousness of teaching work in Higher Education Institutions - private HEIs in Brazil, in contemporary capitalism. To this end, the tendency towards precarious work in contemporary capitalism, the process of capital accumulation in the higher education sector in Brazil, and evidence of the precariousness of teaching work were analyzed, with the research object being a private HEI in São Luís, capital of the State of Maranhão. The methodological procedures included bibliographic and documentary research, including the analysis of the historical evolution of private educational institutions in Brazil from 1995 to 2021. Data collection was carried out through the application of a structured questionnaire prepared based on a precariousness typology social work system consisting of six indicators. It was observed that the extension of the working day, the requirement for versatility, the reduction in decision-making capacity and the excessive number of demands within and outside working hours contribute to a scenario of mental illness with different expressions, which is also aggravated by feeling of insecurity arising from layoffs and the perception that the remuneration is below the work undertaken. All this evidence highlighted in the research shows that the processes of commercialization and oligopolization of private higher education have been harmful to the category of teachers. In addition to this evidence, the perception that the investments made to further boost the growth of distance learning, together with the reduction in the offer of courses and classes in the face-to-face modality demonstrate that this is one of the main strategies of the sponsors to increase the number of students without the need to hire more teachers.